Securing IoT Network using Lightweight MultiFog (LMF) Blockchain Model - Muhammad Yanuar Ary Saputro (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
Security is one of the most important issues in the Internet of Things (IoT). The Mirai botnet case in September 2016 revealed a serious vulnerability in IoT devices. Researchers try to mitigate the issues using several approaches. One of them uses Blockchain for the solution. At first, the integration of the Blockchain on IoT seems promising. However, there are problems in resource consumption and latency. Several solutions emerge to make Blockchain uses low resource consumption i.e., LSB and FogBus. Unfortunately, each solution has its weaknesses. FogBus has a weakness in integrity, whereas LSB has a weakness in its availability when an attack occurs on a broker. We introduce Lightweight Multi-Fog (LMF) Blockchain Model to increase availability in the LSB model. The main idea is increasing the integrity availability by splitting location based on Broadcast Domains while using Fog Computing on each Broadcast Domain. An attack in some Broadcast Domain cannot impact transactions and process in other Broadcast Domain and each Broadcast Domain have its separate transaction and process. LMF enhances the integrity and availability of the Light Blockchain Model. However, it still requires simulations in the future to get a better understanding of LMF performance, resource consumption, and latency